Clinical investigation of α1‐antitrypsin and lactoferrin in gingival sulcus fluid from elderly patients—A preliminary report. Issue 3 (26th August 2019) - Uchiyama, Kimio; Kotani, Kazuhiko; Kato, Toru; Asoda, Seiji
Abstract: Objectives: To compare levels of α1‐antitrypsin (AT) and lactoferrin (LF) in gingival crevicular fluid (GCF) and on the tongue and determine whether MATATACORO® (MA‐T), a stabilized chlorine dioxide solution, affects GCF AT and LF levels. Methodology: The α1‐antitrypsin and lactoferrin levels in GCF and on the tongue were measured for 18 elderly patients (mean age: 83 years) and correlations were analyzed. AT and LF levels in GCF were assessed before and 1 hr after treatment with MA‐T. Results: The α1‐antitrypsin and lactoferrin levels were lower on the tongue than in GCF (median 0.6, 0.4 μg/mL vs median 2.4, 3.6 μg/mL). The respective AT and LF levels in GCF and on the tongue were positively correlated (AT: r = .43, LF: r = .69). GCF AT and LF levels were reduced following MA‐T treatment (AT: median 3.6 and 1.9 μg/mL and LF: 2.3 and 0.4 μg/mL pre‐ and post‐treatment, respectively; both P < .01). Conclusion: The α1‐antitrypsin and lactoferrin levels in GCF were higher than those on the tongue, but AT and LF were detectable for both sampling types. The reduction in GCF AT and LF levels after MA‐T treatment suggests that MA‐T could be used to control periodontal inflammation.